RANCANG BANGUN SMART DOOR LOCK MENGGUNAKAN QR CODE DAN SOLENOID - Atikah Hazarah (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Smart Door Lock is a development of home door lock or padlock conventional manual. This study aims to create an alternative technology at home by utilizing key technologies readily available. This study uses an Arduino Uno microcontroller as the brains of the solenoid, and Android as controller QR Code reader. QR Code reader on Android run using a third party application that is Barcode Scanner. Arduino programming is done using the Arduino IDE. Bluetooth HC 05 is used to connect a barcode scanner app on Android with Arduino. Testing tool is run on Jelly Bean Android platform and the hardware and software components can be run properly. The results of the studies described in the form perncangan home door lock tool automatically uses the QR Code with Barcode Scanner app and Arduino as a control solenoid.